1994
DOI: 10.1007/bf00297187
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of marrow-stromal osteoblasts MBA-15 on three-dimensional carriers

Abstract: The present study describes a new three-dimensional (3-D) culture system that enables the maintenance and phenotypic expression of bone marrow stromal osteoblasts. This culture substratum is advantageous in that it provides suitable conditions for attachment, growth, and differentiation of cells forming 3-D layers. The MBA-15 cell line was grown in unlimited quantities on 3-D Fibro-Cel carriers. These cells mineralized when exposed to ascorbic acid and beta-glycerophosphate (beta GP). Under these mineralizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…This result is consistent with previous studies in which dex and ␤GP induced the osteogenic differentiation of BMSC in monolayers 23 and on 3D matrices. [7][8][9] In previous 3D culture systems, however, ECM mineralization was restricted to an approximately 0.2-mm-thick peripheral layer, both on microcarriers 7,9 and in cell-polymer constructs. 8,10 In the present study, the mineralized foci were distributed throughout the construct volume and represented more than 12% of the total available area in 4-week constructs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This result is consistent with previous studies in which dex and ␤GP induced the osteogenic differentiation of BMSC in monolayers 23 and on 3D matrices. [7][8][9] In previous 3D culture systems, however, ECM mineralization was restricted to an approximately 0.2-mm-thick peripheral layer, both on microcarriers 7,9 and in cell-polymer constructs. 8,10 In the present study, the mineralized foci were distributed throughout the construct volume and represented more than 12% of the total available area in 4-week constructs.…”
Section: Discussionmentioning
confidence: 96%
“…[7][8][9] We previously reported that 3D poly(glycolic acid) (PGA) meshes supported the formation of cartilaginous and bone-like tissues by avian BMSC expanded in the presence of fibroblast growth factor-2 (FGF-2). 10 However, mammalian (bo-vine calf) BMSC cultured on PGA meshes under the same conditions failed to differentiate over 4 weeks in vitro and cell-polymer constructs collapsed.…”
Section: Introductionmentioning
confidence: 99%
“…We used mouse osteogenic cell line MBA-15, which expresses osteoblastic phenotype in vitro and forms bone in vivo [33,34]. On each Ti sample, either coated or uncoated, 7000 cells were seeded.…”
Section: Cell Culture Fixation and Countingmentioning
confidence: 99%
“…In this study, DLDH RGD was prepared by adding GRGDSP residues at the N‐ and C‐termini of DLDH monomer, in order to serve as a molecular bridge between MAB‐15 osteogenic cells and TiO 2 implants . Recently, we have shown that DLDH retains its structural conformation and that its TiO 2 binding is not hindered by the RGD modification .…”
Section: Discussionmentioning
confidence: 99%